Perancangan Multicontrol Pada Lampu Berbasis Internet Of Think (IOT) - Herpendi, Herpendi; Julianto, Veri; Hafizd, Khairul Anwar (STMIK Palangkaraya, 2018)
Technological developments in the communication and information area can changes the lifestyle of the human become the digital lifestyle. Digitalization on the aspects of life can provide convenience for humans. Like the household appliances that can be controlled by a smartphone. In 2015 Nugraha build a light management system with android smartphone via bluetooth media. In addition, the lights are also can be controlled automatically by time and light (LDR). The disadvantages of this system are the lights that can not be used remotely and can not give notice to the home owner about the status â€œon or offâ€ of the light. This research aims to design a multicontrol system to control the light with several media follows : bluetooth, voice, light (LDR), timer, website and SMS as notification of light status. System development method in this research using Waterfall method. The test results using bluetooth, light(LDR), voice, and timer provide a fast response with average less than 2 seconds.